The Impact of Using Dual Axis Solar Trackers on Photovoltaic Efficiency - Sinaga, Denny Haryanto; Tambunan, Handrea Bernando; Sinuraya, Arwadi; Hutajulu, Olnes Yosefa; Sembiring, Muhammad Aulia Rahman; Afrian, T (Jambura Journal of Electrical and Electronics Engineering, 2025)
The utilization of solar energy through photovoltaic (PV) systems continues to face efficiency challenges due to variations in light intensity and the sun’s changing position throughout the day. Static PV panels perform optimally only when positioned perpendicular to incoming sunlight, necessitating an adaptive tracking mechanism. This study designs and evaluates a low-cost dual-axis active solar tracking system employing light-dependent resistors (LDRs) and an Arduino Uno microcontroller to automatically adjust the panel’s orientation in response to solar movement. A five-day performance test was conducted comparing the dual-axis tracker with a fixed-panel system, measuring output power, voltage, current, and overall efficiency. Results show an average power increase of 7.41 W and an efficiency gain of 1.63% with the tracking system. A peak efficiency of 13.49% was recorded under low irradiance conditions, indicating the system’s ability to maintain optimal performance despite fluctuating light. These findings suggest that dual-axis tracking offers a practical and effective solution for enhancing PV efficiency, especially in regions with significant daily variations in solar intensity.Pemanfaatan energi surya melalui sistem fotovoltaik (PV) masih menghadapi tantangan efisiensi akibat variabilitas intensitas cahaya dan posisi matahari sepanjang hari. Panel PV statis hanya menghasilkan daya maksimum saat tegak lurus terhadap arah sinar matahari, sehingga diperlukan sistem pelacakan yang adaptif. Penelitian ini merancang dan menguji sistem pelacak surya aktif dua sumbu berbiaya rendah dengan menggunakan sensor light-dependent resistor (LDR) dan mikrokontroler Arduino Uno, yang secara otomatis mengatur orientasi panel mengikuti pergerakan matahari. Pengujian dilakukan selama lima hari untuk membandingkan kinerja sistem pelacak dengan panel statis, menggunakan parameter daya keluaran, tegangan, arus, dan efisiensi. Hasil menunjukkan peningkatan daya rata-rata sebesar 7,41 W dan efisiensi sebesar 1,63% pada sistem pelacak. Efisiensi tertinggi sebesar 13,49% dicapai pada kondisi iradiasi rendah, mengindikasikan kemampuan sistem dalam menjaga performa optimal di bawah pencahayaan yang tidak stabil. Temuan ini menunjukkan bahwa pelacak dua sumbu merupakan solusi praktis dan efektif dalam meningkatkan efisiensi sistem PV, terutama di wilayah dengan fluktuasi harian intensitas surya yang signifikan.